A Modified Hyaluronic Acid–Based Dissolving Microneedle Loaded With Daphnetin Improved the Treatment of Psoriasis - Peng, Shiya; Cheng, Liuhanghang; Wu, Qian; Li, Yuanchao; Ran, Lei; Wang, Wei; Huang, Ke; Zhu, Rong; Xue, Sihong; Zhou, Chunli; Zhu, Weidong; Cheng, Biao; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Psoriasis is a common chronic immune inflammatory disease. Challenges exist in current treatment of psoriasis, such as difficulties in transdermal drug administration, severe side effects,etc. We hope to achieve better therapeutic outcome for psoriasis treatment by using the modified soluble microneedles (MNs) loaded with treated with daphnetin loaded microneedles, the psoriasis symptoms of mice were significantly reduced, the abnormal proliferation of keratinocytes and the secretion of inflammatory factors were significantly reduced. In vitro, daphnetin is proved to inhibit NF-κB signaling pathway, so as to inhibit the proliferation of HaCaT cells and the release of inflammatory factors, especially CCL20. This research showed that the modified microneedle loaded with daphnetin optimized transdermal drug delivery, and relieved the symptoms of psoriasis more effectively. The novel route of Daph administration provides a future research direction for the treatment of psoriasis.